Pengaruh Manajemen Laba dan Tata Kelola Perusahaan Terhadap Audit Delay - Ika Kristianti; Anis Setianingsih (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to analyze and provide empirical evidence whether the mechanism of corporate governance practices and earnings management has an effect on audit delay. The calculation used in earnings management is discretionary accruals, while the indicators in the governance mechanism are institutional ownership, independent commissioners and audit committees. This study uses the object of research in companies engaged in the tourism, hotel and restaurant sectors listed on the Indonesia Stock Exchange in 2017-2020. Research related to the effect of earnings management and corporate governance on audit delays in tourism, hotel and restaurant sector companies is difficult to find so this research was chosen to be carried out, given the importance of timely information (timeliness) and the transition in the tourism sector due to the COVID-19 pandemic. This research is a qualitative research using purposive sampling technique for sample selection. The data that can be processed are 94 samples. Hypothesis testing using multiple linear regression. The results of the study found that earnings management with discretionary accrual methods and institutional ownership had no effect on audit delay. Meanwhile, the independent board of commissioners and the audit committee have a positive effect on audit delay. The conclusion in this study is that the percentage of institutional ownership does not cause delays in submitting the independent auditor's report. Meanwhile, the higher the total number of independent commissioners and audit committee members, it can slow down the audit, causing audit delay.